A modified sol–gel method using acetone–ethanol mixed solvent for fast constructing nanometric TiO2 shells. Issue 1 (January 2016) - Chen, Wanghui; Takai, Chika; Khosroshahi, Hadi Razavi; Fuji, Masayoshi; Shirai, Takashi
Abstract: We successfully constructed uniform and complete TiO2 shells on SiO2 cores in a short reaction time (2 h) and obtained the core–shell particles with high dispersibility. In this modified sol–gel method, the adopting of ethanol–acetone mixed solvent was critical and advantageous for the fast formation of TiO2 shells. When acetone was controlled at an optimum fraction in solvent (acetone:ethanol=1.2:1 v/v), it not only increased the hydrolysis rate of precursor (i.e., titanium (IV) tetrabutoxide) and the condensation rate of titanium oligomers, but also regulated these two sub-reactions of TiO2 formation to be in balance – and thus suppressed the occurrence of agglomeration during TiO2 coating. In addition, the influence of the concentration of catalyst NH3 and precursor titanium (IV) tetrabutoxide was also investigated. Furthermore, the thickness of TiO2 shells on 366 nm SiO2 cores was varied from 30 to 107 nm by simply adjust the addition volume of precursor, as the regulation role of acetone was widely applicable for different concentration of precursor. Finally, the obtained TiO2 shells were proved to be able to crystallize to anatase shells by calcination, while the core–shell structure showed high stability at high temperature.